2019
DOI: 10.5334/ijc.896
|View full text |Cite
|
Sign up to set email alerts
|

Land Ownership and Catastrophic Risk Management in Agriculture: The Case of Khyber Pakhtunkhwa Province of Pakistan

Abstract: The agricultural sector faces numerous threats arising mainly due to adverse weather conditions. These climatic risks are usually beyond the control of farmers and are mostly uncertain. Managing these risks and uncertainties is crucial in an effort to alleviate poverty and ensure food security for the masses who depend on farm sector for their livelihoods. Land tenure agreements along with other socioeconomic factors play an important role in farmers' decisions to adopt risk coping tools. This study is aimed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Institutional characteristics involved variables such as access to extension, information, urban linkage, and social participation. All of these variables were previously used in multiple studies related to risk perception and management [ 4 , 12 , 13 , 14 , 20 , 23 , 42 , 43 ]. Access extension was taken if the extension department visited or contacted in any form each month: if yes, then = 1; otherwise, 0.…”
Section: Description Of Variablesmentioning
confidence: 99%
See 3 more Smart Citations
“…Institutional characteristics involved variables such as access to extension, information, urban linkage, and social participation. All of these variables were previously used in multiple studies related to risk perception and management [ 4 , 12 , 13 , 14 , 20 , 23 , 42 , 43 ]. Access extension was taken if the extension department visited or contacted in any form each month: if yes, then = 1; otherwise, 0.…”
Section: Description Of Variablesmentioning
confidence: 99%
“…Farming is the most dominant source of income and is responsible for feeding the ever-growing population of Pakistan; it is imperative to secure it from environmental hazards and climatic uncertainty [ 5 , 6 ]. Previous studies have suggested the adoption of multiple risk management strategies to minimize climatic risks [ 10 , 11 , 12 , 13 ]. Risk management can be termed as an approach for agricultural risk reduction and enhancing food security [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the first study from Pakistan discussed the issue of climate change adaptation problems faced by rain-fed farmers in plain areas of Punjab Pakistan, the second study has focused on land ownership and catastrophic risk management in agriculture from analysis of the Case of rugged areas in Khyber Pakhtunkhwa Province of Pakistan (Ullah et al 2019). The paper identifies a number of threats in agriculture sector from the growing instability in production levels arising mainly due to adverse weather conditions and these climatic risks are usually beyond the control of farmers and are mostly uncertain.…”
mentioning
confidence: 99%